Subgroups of persistent juvenile offenders: latent class analysis of repeated juvenile assessment center entries - Dembo, Richard (Deviant behavior, 2024)
Many juvenile justice agencies rely on risk assessments to inform administrative decisions about youth placement. While many studies within recent years have explored patterns in criminal offending over time, little research has explored the heterogeneity in youth placement decisions by the juvenile justice system. There is a need to document the patterns, levels, and trends in offense risk among youth entering and reentering the justice system. This study used latent class analysis to identify subgroups of n = 388 male juveniles repeatedly entering a U.S. juvenile justice system based on youth placement decisions. The persistent juvenile offenders were best classified into either a moderately increasing risk placement group or a severely increasing risk placement group. The moderately increasing group experienced more bullying involvement, while the severely increasing group was older and experienced more sexual assault, sexual partners, treatment for drug use problems, and elevated depression. Policy recommendations are made.